1984
DOI: 10.1897/1552-8618(1984)3[617:bmfdto]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Biological Methods for Determining Toxicity of Contaminated Freshwater Sediments to Invertebrates

Abstract: Methods are presented for using Daphnia magna, Hyalella azteca, Gammarus lacustris, Chironomus tentans and Hexagenia limbata to screen freshwater sediments for acute and chronic toxicity, bioaccumulation potential and insitu toxicity. The 48-h Daphnia tests are recommended as inexpensive, uncomplicated and sensitive acute methods. Hyalella and Chironomus are the recommended benthic test organisms, as they are easy to rear and test, they remain in intimate contact with the sediment and they exhibit high control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
75
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 9 publications
(15 reference statements)
0
75
0
Order By: Relevance
“…tentans distribution in a heavy metal contaminated lake showed smaller population sizes in the most heavily contaminated sediments (Wentsel et al ., 1977a) . Many laboratory studies of C. tentans survival and growth in sediments contaminated with heavy metals and/or organic compounds have demonstrated decreased survival and/or reduced growth of larvae (e .g ., Wentsel et al ., 1977b ;Cairns et al ., 1984 ;Adams et al ., 1985Adams et al ., , 1986Giesy et al ., 1988Giesy et al ., , 1990Nebeker et al ., 1984aNebeker et al ., , 1988Hoke et al ., 1990 ;West et al ., 1993) . Lower numbers of emerging adults have also been observed following exposure of larvae to sediments contaminated with heavy metals (Wentsel et al ., 1978) and to artificial substrates contaminated with DDE (Derr & Zabik, 1972) .…”
Section: Introductionmentioning
confidence: 99%
“…tentans distribution in a heavy metal contaminated lake showed smaller population sizes in the most heavily contaminated sediments (Wentsel et al ., 1977a) . Many laboratory studies of C. tentans survival and growth in sediments contaminated with heavy metals and/or organic compounds have demonstrated decreased survival and/or reduced growth of larvae (e .g ., Wentsel et al ., 1977b ;Cairns et al ., 1984 ;Adams et al ., 1985Adams et al ., , 1986Giesy et al ., 1988Giesy et al ., , 1990Nebeker et al ., 1984aNebeker et al ., , 1988Hoke et al ., 1990 ;West et al ., 1993) . Lower numbers of emerging adults have also been observed following exposure of larvae to sediments contaminated with heavy metals (Wentsel et al ., 1978) and to artificial substrates contaminated with DDE (Derr & Zabik, 1972) .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the test species ideally should be closely associated with sediments, have widespread distribution and be easily cultured and handled in the laboratory. Nebeker et al (1984) suggested that the amphipod Hyalella azteca and the chironomid Chironomus tentans were good candidates for freshwater sediment toxicity tests, and Nelson et al (1991) recently published an informative review detailing the use of H. azteca and C. tentans in solid phase sediment toxicity tests. Other researchers also have suggested that different oligochaete species may be useful for acute and/or chronic testing of freshwater sediments (Chapman et al, 1982a(Chapman et al, , 1982bWiederholm et al 1987;Keiltyet al 1988aKeiltyet al , 1988bReynoldson et al 1991;Smith et al, 1991;Phipps et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…It is recognized that ecotoxicological testing needs to be based on standard test organisms and to be supplemented by the use of some ambient bioassay. Furthermore a battery of tests should be used in order to ensure that the 'no effect level' in one test will also be discriminated at several trophic levels (Nebecker et al, 1984;Cairns & Pratt, 1989;Dutka et al, 1989;Sloterdijk et al, 1989;Giesy & Hoke, 1989). In this paper we concentrate on the ecotoxicity associated with suspended sediments of the Rhone River as determined by three acute bioassay procedures.…”
Section: Introductionmentioning
confidence: 99%